Complement‐mediated hemolysis persists year round in patients with cold agglutinin disease. Issue 1 (23rd November 2021) - Röth, Alexander; Fryzek, Jon; Jiang, Xiaohui; Reichert, Heidi; Patel, Parija; Su, Jun; Morales Arias, Jaime; Broome, Catherine M.
Abstract: Background: Cold agglutinin disease (CAD) is a rare autoimmune hemolytic anemia mediated by immunoglobulin M autoantibodies that bind to the "I" antigen on erythrocytes. IgM binding results in either agglutination at ≤37°C, activation of the classical complement pathway, or both. Patients with CAD can have transient agglutination‐mediated circulatory symptoms triggered by exposure to cold conditions. Separately, patients with CAD can experience complement‐mediated symptoms such as anemia, hemolysis, and fatigue, but the effect of the season on these complement‐mediated manifestations of CAD and clinical outcomes is not well understood. Methods: Using data from the Optum® de‐identified Electronic Health Record dataset, we compared hemoglobin, markers of hemolysis (bilirubin and lactate dehydrogenase [LDH]), and healthcare resource utilization (HRU) between seasons for 594 patients (62% female; 66% aged ≥65 years) with CAD (defined as having CAD‐related terms in their clinical notes on ≥3 separate occasions between December 2008 and May 2016). Laboratory parameters and HRU were compared between seasons using multivariate regression models. Results: Estimated median hemoglobin (9.87 g/dL in summer and 9.86 g/dL in winter; P = 0.944) and bilirubin (1.04 mg/dL in summer and 1.09 mg/dL in winter; P = 0.257) were similar in winter versus summer. While LDH was statistically significantly higher in winter compared with summer ( P < 0.001), the estimated median value was above normal for both seasons (309 U/L in summer and 367 U/L in winter). HRU measures and transfusion and thromboembolism rates were similar across seasons. Conclusions: Patients with CAD had evidence of persistent chronic hemolysis, HRU, and thromboembolism risk year round. Abstract : See article on page 2–10, in this issue